Sleep and performance in simulated Navy watch schedules. (February 2017) - Skornyakov, Elena; Shattuck, Nita L.; Winser, Michael A.; Matsangas, Panagiotis; Sparrow, Amy R.; Layton, Matthew E.; Gabehart, Rylie J.; Van Dongen, Hans P.A.
Highlights: We compared sleep, vigilance and sleepiness in simulated Navy watch schedules. Sleep opportunities were limited; average sleep duration was 5.6 h per watch day. Sleep restriction resulted in build-up of vigilance impairment across watch days. Vigilance was more variable in the 5/15 than in the 3/9 watch schedule. Subjective sleepiness did not accurately reflect vigilance impairment. Abstract: To operate Navy ships 24 h per day, watchstanding is needed around the clock, with watch periods reflecting a variety of rotating or fixed shift schedules. The 5/15 watch schedule cycles through watch periods with 5 h on, 15 h off watch, such that watches occur 4 h earlier on the clock each day – that is, the watches rotate backward. The timing of sleep varies over 4-day cycles, and sleep is split on some days to accommodate nighttime watchstanding. The 3/9 watch schedule cycles through watch periods with 3 h on, 9 h off watch, allowing for consistent sleep timing over days. In some sections of the 3/9 watch schedule, sleep may need to be split to accommodate nighttime watchstanding. In both the 5/15 and 3/9 watch schedules, four watch sections alternate to cover the 24 h of the day. Here we compared sleep duration, psychomotor vigilance and subjective sleepiness in simulated sections of the 5/15 and 3/9 watch schedules. Fifteen healthy male subjects spent 6 consecutive days (5 nights) in the laboratory. Sleep opportunities were restricted to an average of 6.5 h daily. Actigraphically estimated sleep duration was 5.6 h per watch day on average, with no significant difference between watch sections. Sleep duration was not reduced when sleep opportunities were split. Psychomotor vigilance degraded over watch days, and tended to be more variable in the 5/15 than in the 3/9 watch sections. These laboratory-based findings suggest that Navy watch schedules are associated with cumulative sleep loss and a build-up of fatigue across days. The fixed watch periods of the 3/9 watch schedule appear to yield more stable performance than the backward rotating watch periods of the 5/15 watch schedule. Optimal performance may require longer and more consistent daily opportunities for sleep than are typically obtained in Navy operations.